Imprisonment of Tax Non-Payers – an Abuse of Power or a Measure of Legal Discipline? - Kubiak, Przemysław (Studia Ceranea, 2012)
In the field of taxation there existed many casuistic crimes of Roman criminal law, committed both by tax payers and tax collectors, but non-payment of taxes was not one of them. As a rule taxpayers risked confiscation of property by avoiding the fulfillment of their obligation. There exists some historical evidence, however, which suggests the possibility of imprisonment of taxpayers. Was it possible to inflict criminal punishments in such cases? Legal texts give some reflections to the contrary– Roman emperors prohibited the use of imprisonment in non-criminal matters. The number of these prohibitions indicates, that there were many situations of this kind. It seems that especially in the provinces the governors abused their power and used illegal measures, such as tortures, whipping and imprisonment, to force citizens to pay taxes.